ANALYSIS OF THE LIFESTYLE OF ANIME AND MANGA FANS IN SURAKARTA CITY - Hidayatullah, Adam Zulkarnaen (JURNAL SOCIUS, 2023)
This research is motivated by the phenomenon of the emergence of Otaku who are fans of Japanese sub-culture in the form of anime and manga in Surakarta City. How is their behavior or lifestyle and what are their reasons for identifying themselves as Otaku. This research will describe the lifestyle of Otaku and how they interpret anime, manga and themselves as Otaku. This qualitative research uses an ethnographic approach in which data sources are events, informants and documents. This study used a purposive sampling technique in which researchers conducted interviews, observations and documentation while researching. The data validity technique was carried out by triangulating data from documents with interview results. This study found that some otaku interpret anime and manga as more than just entertainment.